PRODUCTION AND COMPOSITION OF MILK FROM COWS FED SUGARCANE SUPPLEMENTED WITH NO PROTEIN NITROGEN SOURCES OF DIFFERENT RUMINAL DEGRADABILITY / Produção e composição do leite de vacas alimentadas com cana de açúcar suplementada com fontes de ... - FALEIRO NETO, J. A.; REIS, R. B.; SAMPAIO, I. B. M.; SATURNINO, H. M.; SOUSA, B. M.; MOREIRA, E. M. (Ars Veterinaria, 2013)
A cana de açúcar (Sacharum officinarum L.) apresenta elevado potencial de produção de matéria seca (MS) e energia por unidade de área, fácil cultivo e manutenção do seu valor nutricional durante todo ano e principalmente em períodos de estiagem. Devido ao baixo teor de proteína bruta, a correção desta fração (proteína) deve ser realizada visando otimizar a relação energia:amônia e maximizar os processos fermentativos microbianos no rúmen. O objetivo do presente estudo foi avaliar a eficiência de fontes e níveis de NNP (ureia e OptigenII®), acrescidos na cana de açúcar (0,3; 0,6 e 0,9% - na matéria natural) em dietas com relação volumoso:concentrado 50:50 sobre o consumo de matéria seca (CMS), matéria orgânica (CMO), fibra em detergente neutro (CFDN), proteína bruta (CPB), extrato etéreo (CEE), produção e composição do leite e, níveis plasmáticos de nitrogênio uréico (NUP). Sete vacas da raça Holandesa com 583 kg de peso corporal mantidas em tie stall com 45 + 12 dias em lactação e 25 kg de leite foram distribuídas em delineamento tipo blocos incompletos balanceados com os seguintes tratamentos: ureia 0,3; 0,6 e 0,9% ou Optgen IIÒ nos mesmos níveis e uma dieta controle sem adição de N a cana-de-açucar (controle). O CMS em kg ou em % PC não apresentou diferença entre os tratamentos. Houve diferença para o CFDN em kg/dia e não houve diferença (P>0,05) para o CFDN em % do peso vivo. Não houve diferença (P>0,05) para o CMO e CPB. Não houve diferença (P>0,05) para produção de leite. Para os teores de gordura, lactose, ESD e ST não houve diferença (P>0,05). Houve diferença (P>0,05) para o teor de proteína do leite. O nível de 0,3% de ureia é suficiente para vacas produzindo ao redor de 25 kg/leite/dia. SUMMARY Sugarcane (Sacharum officinarum L.) has high production potential of dry matter (DM) and energy per unit area; it is also easy to grow and maintains the nutritional value throughout the year, especially during drought periods. Because it has low protein content, this fraction (protein) should be corrected to optimize the energy:ammonia ratio and maximize rumen microbial fermentation processes. The objective of this study was to evaluate the efficiency of sources and levels of NPN (urea and OptigenII ®) added to sugarcane (0.3, 0.6 and 0.9% - as fed) in diets with roughage: concentrate ratio 50:50 on dry matter intake (DMI), organic matter (OM), neutral detergent fiber (NDF), crude protein (CP), ether extract (EE), production and composition of milk and plasma urea nitrogen (PUN). Seven multiparous Holstein cows with 45+ 12 days in milk and 25 kg of milk per day were used. The cows were distributed in seven treatments in a balanced incomplete block design. All the cows, housed in a tie stall barn, were fed diets based on fresh chopped sugarcane with increasing levels of urea or OptigenII®: 0.3%, 0.6%, 0.9% and a control group without urea. The level of urea or OptigenII® in the diets was based on the amount of sugarcane in as fed basis. The dry matter intake (DMI) was not affected by the experimental diets (P>0.05) and ranged from 18.05 to 18.70 kg per day. DMI expressed as percentage body weight ranged from 2.95 to 3.45%. The NDF intake kg per day was higher for the control diet compared to the 0.9% of OptigenII® diet (P<0.05); however, no difference was detected for NDF intake as percentage of body weight. The milk yield and 3.5 % fat corrected milk yield ranged from 22.23 to 25.58 kg per day and from 19.9 to 21.6 kg per day, respectively, without difference between diets. Milk fat percentage and production ranged from 2.92% to 3.4% and from 0.72 to 0.78 kg per day, respectively. Milk protein percentage and production ranged from 2.7 to 3.11% and from 0.73 to 0.77 kg per day, with coefficient of variation of 1.08% and 16.2%, respectively. The inclusion of 0.9% of urea in the diet resulted in the highest level of milk protein. Different sources of non-protein nitrogen can be used in the diets of dairy cows producing up to 25 kg of milk per day without changing milk yield and composition.